Research on Tobacco in Indonesia : An Annotated Bibliography and Review of Research on Tobacco Use, Health Effects, Economics, and Control Efforts - Djutaharta, Triasih; Viriya Surya, Henry (World Bank, Washington, DC, 2013)
This report summarizes 46 studies on various aspects of tobacco in Indonesia published since 1990. Studies are arranged alphabetically by author's last name. The studies include tobacco use surveys, studies on tobacco-related mortality and diseases including costs, and health problems associated with environmental tobacco smoke. Some studies cover interventions to reduce tobacco use, and tobacco control policies, including price increases. Some studies look at specific groups such as children, street vendors, drivers, youth, athletes or nurses. Studies were traced using bibliographies of an initial set of studies collected